Adherence to immunosuppressive therapy following liver transplantation: an integrative review - Ramon Antônio Oliveira; Ruth Natália Teresa Turrini; Vanessa de Brito Poveda
ABSTRACT Objective: to investigate the evidence available in the literature on non-adherence to immunosuppressive therapy among patients undergoing liver transplantation. Method: integrative literature review, including research whose sample consisted of patients aged over 18 years undergoing liver transplantation. It excluded those containing patients undergoing multiple organ transplants. For the selection of articles, Medline / Pubmed, CINAHL, LILACS, Scopus and Embase were searched. The search period corresponded to the initial date of indexation of different bases, up to the deadline of February 10, 2015, using controlled and uncontrolled descriptors: liver transplantation, hepatic transplantation, liver orthotopic transplantation, medication adherence, medication non-adherence, medication compliance and patient compliance. Results: were located 191 investigations, 10 of which met the objectives of the study and were grouped into four categories, namely: educational process and non-adherence; non-adherence related to the number of daily doses of immunosuppressive medications; detection methods for non-adherence and side effects of therapy. Conclusion: there were risk factors related to the health service, such as control and reduction of the number of doses; related to the individual, such as being male, divorced, alcohol or other substances user, exposed to low social support and being mentally ill.